Health insurance for the poor in India - Rajeev Ahuja (Indian Council for Research on International Economic Relations (ICRIER), 2004)
Community based health insurance (CBHI) is more suited than alternate arrangements to providing health insurance to the low-income people living in developing countries. The universal health insurance scheme, launched recently by the Prime Minister of India, is only one of the forms that CBHI can take. While analysing the proposed scheme, we examine alternate forms of CBHI schemes prevalent in the country.The development of private health insurance market in the country will not leave the poor unaffected. Insurance sector reform can affect the poor through its effect on the provision of health services (i.e., cost, quality and access) used by the low-income people as well as through its access to financing of health care. In this paper we also explore how insurance sector reforms alter health insurance prospects facing the poor in India, and what changes on the health front affecting the poor have happened or are likely to happen as a result of insurance sector reforms. We conclude that in diverse settings of India all forms of CBHI have a role to play and therefore need to be encouraged by the government through appropriate interventions. Formal insurance providers can also be reigned to serve low-in comepopulation. At the same time, developments in formal health insurance market need to be guided so as to minimise cost escalation of health care provision
Keywords: I1; I3; G1; 330; Health Insurance; Low-income people; poverty; risk and insurance; insurance schemes; Niedrigeinkommen; Armut; Armutsbekämpfung; Krankenversicherung; Versicherungsmarkt; Indien